Business in Ecological Sphere: it's Role in World Politics - A. A. Coolinich (Vestnik MGIMO-Universiteta)
The article deals with major approaches to defining the phenomenon of “green business” and its potential role in the sphere of alternative energy sector in world politics. The author stresses the “classic business” approaches to solving global ecological problems and shifting to environment friendly production mechanisms